2011
DOI: 10.1016/j.virol.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The early UL3 gene of equine herpesvirus-1 encodes a tegument protein not essential for replication or virulence in the mouse

Abstract: The UL3 gene of equine herpesvirus-1 (EHV-1) is retained in the genome of defective interfering particles and encodes a ~33 kDa myristylated protein. Further characterization showed that the UL3 gene is trans-activated only by the sole immediate early (IE) protein and encodes an early protein that is dispensable for EHV-1 replication and localizes in the tegument of purified virions. UL3-deleted EHV-1 (vL11ΔUL3) exhibits properties of host cell tropism, plaque size, and growth kinetics similar to those of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Circ is a small, myristylated protein non-essential for replication in tissue culture [ 55 ] that localizes to the virion [ 56 ]. The homolog protein in equine herpesvirus-1 (EHV-1), UL1, also localizes in the tegument [ 57 ], in contrast to ORF-2 of varicella zoster virus (VZV) which does not [ 58 ]. Circ's function is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Circ is a small, myristylated protein non-essential for replication in tissue culture [ 55 ] that localizes to the virion [ 56 ]. The homolog protein in equine herpesvirus-1 (EHV-1), UL1, also localizes in the tegument [ 57 ], in contrast to ORF-2 of varicella zoster virus (VZV) which does not [ 58 ]. Circ's function is not clear.…”
Section: Discussionmentioning
confidence: 99%
“… b Function is assigned primarily from published data for proteins of herpes simplex virus 1 (HSV-1) ( 23 , 43 , 44 ). The discovery and function of EHV-1 IR2 ( 25 , 26 ), IR3 ( 27 29 ), UL1 and UL2 ( 39 ), UL3 ( 45 ), UL11 ( 46 ), UL20 ( 47 ), UL31 ( 48 ), UL34 ( 49 ), US4 (gp2) ( 50 ), and US6 (gI) and US7 (gE) ( 37 ) were reported previously . –, not present .…”
Section: Resultsmentioning
confidence: 55%
“…We recently observed that EHV-1 early regulatory proteins IR2P, UL3P, and UL4P act as the negative regulatory protein for EHV-1 gene expression (Ahn et al, 2011; Charvat et al, 2011; Kim et al, 2006, 2011). Unlike the IEP, these negative regulatory proteins have a broad inhibitory function that may prevent transcription of a variety of EHV-1 promoters by interfering with the interaction between the GTFs.…”
Section: Discussionmentioning
confidence: 99%